Strength and biomechanical risk factors for noncontact ACL injury in elite female footballers: A prospective study - Collings, T. J.; Diamond, L. E.; Barrett, R. S.; Timmins, R. G. Hickey, M. J. T.; Du Moulin, W. S.; Williams, M. D.; Beerworth, K. A.; Bourne, M. N. (Medicine & Science in Sports & Exercise, 2022)
Purpose This study aimed to determine if a preseason field-based test battery was prospectively associated with noncontact anterior cruciate ligament (ACL) injury in elite female footballers.